Electronic commerce‐enabled supply chain process integration and business value - Ghobakhloo, Morteza; Sabouri, Mohammad Sadegh; Tang, Sai Hong; Amirizadeh, Khosro (Emerald Group Publishing, 2011)
Purpose: The purpose of this paper is to develop and test a model to analyze the relationships between three aspects of technical electronic commerce (EC)‐based information system (IS) resources; the supply chain process integration; and business value. Design/methodology/approach: The paper is consistent with the perspective on IS‐enabled organizational capabilities and resource based view of the firm. A questionnaire‐based survey was conducted to collect data from 214 supply chain, logistics, or procurement/purchasing managers of leading manufacturing firms. Findings: The findings suggest that supply chain process integration, a key EC‐enabled organizational capability, can enhance business value. We found that this capability serve as a catalyst in transforming technical EC‐based IS resources (technical quality of EC applications, EC advancements, and EC alignment) into higher value for a firm. Research limitations/implications: Among other limitations, this paper does not address human IS resources as the other potential determinants of firm's supply chain capabilities. Moreover, this study relies on cross‐sectional data. Practical implications: The results suggest that supply chain process integration is an important intermediate organizational capability through which value of EC‐based IS resources can be materialized. The technical aspects of EC‐based IS resources need to be developed to effectively form supply chain capabilities. Originality/value: The paper is perhaps one of the first to show theoretically and empirically how firms, in particular in developing countries, can generate business value from EC‐enabled supply chain process integration; also it broadens the scope of EC alignment in relation to process integration and business value to the entire supply chain.